On Almost Maximum Distance Separable Codes - Al-seraji, N. (Iraqi Journal of Science, 2023)
The main goal of this paper is to make link between the subjects of projectivegeometry, vector space and linear codes. The properties of codes and some examplesare shown. Furthermore, we will give some information about the geometricalstructure of the arcs. All these arcs are give rise to an error-correcting code thatcorrects the maximum possible number of errors for its length.